2020
DOI: 10.1101/2020.05.13.093195
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ChAdOx1 nCoV-19 vaccination prevents SARS-CoV-2 pneumonia in rhesus macaques

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) emerged in December 20191,2 and is responsible for the COVID-19 pandemic3. Vaccines are an essential countermeasure urgently needed to control the pandemic4. Here, we show that the adenovirus-vectored vaccine ChAdOx1 nCoV-19, encoding the spike protein of SARS-CoV-2, is immunogenic in mice, eliciting a robust humoral and cell-mediated response. This response was not Th2 dominated, as demonstrated by IgG subclass and cytokine expression profiling. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
285
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(303 citation statements)
references
References 14 publications
11
285
0
7
Order By: Relevance
“…Lung tissues were collected from all animals at 7 days post challenge and sections examined for pathologic changes within the upper and lower airways. Consistent with Rev08 10 previous reports of SARS-CoV-2 infection in rhesus macaques [5][6][7][8][9][10] placebo control animals had moderate to severe inflammation that involved the mucosa of the bronchi, perivascular mononuclear infiltrate with mixed infiltrates of macrophages and neutrophils within the alveoli. In contrast, there was little, or no inflammation observed in the lungs of macaques immunized with NVX-CoV2373 vaccine 7 days post challenge (Figure 2).…”
Section: Lung Pathologysupporting
confidence: 88%
“…Lung tissues were collected from all animals at 7 days post challenge and sections examined for pathologic changes within the upper and lower airways. Consistent with Rev08 10 previous reports of SARS-CoV-2 infection in rhesus macaques [5][6][7][8][9][10] placebo control animals had moderate to severe inflammation that involved the mucosa of the bronchi, perivascular mononuclear infiltrate with mixed infiltrates of macrophages and neutrophils within the alveoli. In contrast, there was little, or no inflammation observed in the lungs of macaques immunized with NVX-CoV2373 vaccine 7 days post challenge (Figure 2).…”
Section: Lung Pathologysupporting
confidence: 88%
“…Multiple studies employing a variety of vaccine formulations and modalities have now demonstrated that SARS-CoV-2 viral neutralization titers in small animals including mice and guinea pigs are predictive of immunogenicity in macaques and humans ( Figure 5E) [17][18][19][20]22,23,[33][34][35][36][37][40][41][42][43]45 . Despite promising immunogenicity in several cases, all of the above liquid formulations were either refrigerated or frozen prior to use.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, only one dose of Ad-vectored vaccines has been administered in early preclinical challenge studies or clinical studies against emerging or outbreak pathogens 2-5 . Rhesus macaques immunised with a single dose of ChAdOx1 nCoV-19 were protected against pneumonia but there was no impact on nasal virus titers after high dose challenge to both the upper and lower respiratory tract 6 . To increase antibody titres and longevity of immune responses, a booster vaccination may be administered.…”
Section: Introductionmentioning
confidence: 96%